Can citizen science work? Perceptions of the role and utility of citizen science in a marine policy and management context - Vann-Sander, S.; Clifton, J.; Harvey, Euan (Pergamon, 2016)
Citizen science is often envisaged as a means to promote community participation in marine resource management. However, its potential contribution in this field is limited by stakeholders' perceptions on the value and utility of data collected in this way. This is exacerbated in the Australian context by insufficient resources to inform management regarding the country's extensive coastline. The present study employs a systems thinking methodology to map stakeholders' conceptual models of citizen science in Western Australia. This shows that a fundamental policy shift must occur n order to encompass the views of all stakeholders and converge on a common understanding of its role and utility of citizen science beyond the current science-centric discourse.